2019
DOI: 10.7181/acfs.2018.02355
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic subcutaneous emphysema after liposuction

Abstract: Traumatic subcutaneous emphysema, which is the infiltration of air into subcutaneous tissues due to trauma, is caused by various factors such as chest and/or abdominal trauma, facial fractures, and barotrauma caused by mechanical ventilation. In this case report, a 32-year-old woman developed traumatic subcutaneous emphysema after undergoing abdominal liposuction at a local clinic. She was subsequently admitted to Busan Paik Hospital, and with early diagnosis and conservative treatment, she was discharged on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…The rate of pneumoperitoneum is likely even lower, with the literature limited to a few case reports and series. 2,[9][10][11][12][13] The presence of abdominal wall abnormalities, prior surgery, and liposuction being performed on the flanks, back, and axilla has been shown to be associated with the violation of the thoracic and abdominal cavities. 1,6 The current case highlights the importance of keeping a wide differential diagnosis when evaluating patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of pneumoperitoneum is likely even lower, with the literature limited to a few case reports and series. 2,[9][10][11][12][13] The presence of abdominal wall abnormalities, prior surgery, and liposuction being performed on the flanks, back, and axilla has been shown to be associated with the violation of the thoracic and abdominal cavities. 1,6 The current case highlights the importance of keeping a wide differential diagnosis when evaluating patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Mentz et al 1 reported the rate of pneumothorax to be 0.04% after liposuction in a case series of over 16,000 patients. The rate of pneumoperitoneum is likely even lower, with the literature limited to a few case reports and series 2,9–13 . The presence of abdominal wall abnormalities, prior surgery, and liposuction being performed on the flanks, back, and axilla has been shown to be associated with the violation of the thoracic and abdominal cavities 1,6 …”
Section: Discussionmentioning
confidence: 99%
“…The complications following VASER-assisted liposuction are variable and small amount of subcutaneous emphysema can be present; however, extensive subcutaneous emphysema is extremely rare. 3,4 The patient was also treated with J-Plasma ® for skin retraction and tightening. This device instantly heats tissue to temperatures greater than 85°C for 0.040 to 0.080 seconds producing soft tissue contraction.…”
mentioning
confidence: 99%
“…Recently, Kim et al 3 reported a case of traumatic subcutaneous emphysema following suction-assisted liposuction. In their report, the mechanism of patient’s subcutaneous emphysema following liposuction was due to entry of air via the skin incision, its entrapment due to negative pressure differential, and air accumulation in fascial planes, eventually leading to subcutaneous emphysema.…”
mentioning
confidence: 99%